2017
DOI: 10.1002/cssc.201700120
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles for Covalent Organic Frameworks in Energy Storage Applications

Abstract: Covalent organic frameworks (COFs) are an exciting class of porous materials that have been explored as energy-storage materials for more than a decade. This review discusses efforts to develop these materials for applications in gas and electrical power storage. Some of the design strategies for developing the gas sorption properties of COFs and mechanistic studies on their formation are also discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
120
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 157 publications
(168 reference statements)
1
120
0
Order By: Relevance
“…The formation of the imine-based H 2 P-COF-BATA was confirmed by 13 Cc ross polarization magic angle spinning ( 13 CC P-MAS) solid-stateN MR spectroscopy,F ourier transform infrared spectroscopy (FTIR),p owder X-ray diffraction (PXRD), nitrogen adsorption isotherm measurements ( Figure 2) and X-ray photoelectron spectroscopy (XPS) (Figure 3, FigureS2-S7 in Supporting Information). The 13 CC P-MASs olid-stateN MR spectrum of H 2 P-COF-BATA ( Figure S8)s hows ag roup of signals correspondingtothe sp 2 carbon atoms of the materialand confirms the formation of the imine bond by the characteristics ignal at d = 163 ppm, which corresponds to the chemicals hift of the -C=Nc arbon.T he FTIR spectrum shows the disappearanceo f the characteristic bands of the starting materials, that is, the carbonyl bands at 1668a nd 1679 cm À1 from the aldehydes and the NH 2 stretching band at 3300-3400 cm À1 from the amines;i na ddition, it can be observed the emergence of the characteristic stretching vibration of the C=Nb ond at 1614 cm À1 .A fter sulfur incorporation, the main absorption bands of H 2 P-COF-BATA remainu nchanged andanew band is observed at 670 cm À1 , assigned to the vibration of the CÀS bond ( Figure 2b).…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…The formation of the imine-based H 2 P-COF-BATA was confirmed by 13 Cc ross polarization magic angle spinning ( 13 CC P-MAS) solid-stateN MR spectroscopy,F ourier transform infrared spectroscopy (FTIR),p owder X-ray diffraction (PXRD), nitrogen adsorption isotherm measurements ( Figure 2) and X-ray photoelectron spectroscopy (XPS) (Figure 3, FigureS2-S7 in Supporting Information). The 13 CC P-MASs olid-stateN MR spectrum of H 2 P-COF-BATA ( Figure S8)s hows ag roup of signals correspondingtothe sp 2 carbon atoms of the materialand confirms the formation of the imine bond by the characteristics ignal at d = 163 ppm, which corresponds to the chemicals hift of the -C=Nc arbon.T he FTIR spectrum shows the disappearanceo f the characteristic bands of the starting materials, that is, the carbonyl bands at 1668a nd 1679 cm À1 from the aldehydes and the NH 2 stretching band at 3300-3400 cm À1 from the amines;i na ddition, it can be observed the emergence of the characteristic stretching vibration of the C=Nb ond at 1614 cm À1 .A fter sulfur incorporation, the main absorption bands of H 2 P-COF-BATA remainu nchanged andanew band is observed at 670 cm À1 , assigned to the vibration of the CÀS bond ( Figure 2b).…”
Section: Resultsmentioning
confidence: 92%
“…[11] In recent years, due to the unique characteristics of COFs, scientists from many different areas, including synthetic chemists and materials scientists, have jumped into the field developing av ariety of materials with applications in areas such as catalysis, storagea nd separation of gases, separation from solutions, optoelectronics, drug delivery, or sensing among others. [12] In this respect, it is worth mentioning that 2D-COFs have also found applicationsi nt he field of electrochemical energy storage, [13] where 2D-COFsh ave been used not only as active materials [14] but also as hosts for active materials [10,15] in rechargeable Li-ion batteries.…”
Section: Introductionmentioning
confidence: 99%
“…The uniform and controlled porosity as a result of their crystallinity makes COFs perfect candidates for separation of gasses, as well as purification of liquids . Furthermore, redox‐active COFs with a high surface area have become an increasingly interesting class of material for electrochemical energy storage devices . Whatever the application, a high thermal and chemical stability of the structural linkages of COFs is very important and this drove the direction of the research as reported in this paper.…”
Section: Methodsmentioning
confidence: 91%
“…3 Furthermore, redox-active COFs with a high surface area have become an increasingly interesting class of material for electrochemical energy storage devices. 4,5 Whatever the application, a high thermal and chemical stability of the structural linkages of COFs is very important and this drove the direction of the research as reported in this paper.…”
mentioning
confidence: 90%
“…Merging the properties of three‐dimensional buckyballs (or buckybowls) and covalent‐organic frameworks (COFs) provides access to a novel class of materials combining ultrafast energy/electron transport characteristic of three‐dimensional (3D) fulleretic linkers with high modularity, crystallinity, and surface area, which are intrinsic properties of COFs . The precise donor–acceptor alignment achieved in the materials is imposed by the rigid COF scaffold and is crucial for efficient energy or charge transfer as it can influence the distance of exciton diffusion, π–π stacking, or Förster radius, and as a result, can enhance device performance …”
Section: Introductionmentioning
confidence: 99%